Papillary renal adenoma in a toco toucan (Ramphastos toco) - Arenales, Alexandre; Toledo, Frank A. de O.; Oliveira, Ayisa R. de; Paula, Nayara F. de; Oliveira, Lucas B. S. de; Coelho, Carlyle M.; Tinoco, Herlandes P.; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2018)
Primary renal neoplasms are infrequent in domestic animals and birds, being budgerigars an exception. This report describes a papillary renal adenoma in a toco toucan (Ramphastos toco), which was euthanized due to poor prognosis after surgical intervention of phalanx fractures in both wings. Grossly, the caudal pole of the right kidney had a nodular lesion measuring 3.5 x 1.7 x 1.5 cm. Microscopically, there was a well delimited neoplasm arranged in large and coalescent papillary structures composed by a single layer of epithelial cells. There was mild to moderate nuclear and cytoplasmic pleomorphism, whereas mitotic figures were absent. In conclusion, this tumor was considered as an accidental finding, which is similar to the majority of adenomas reported in domestic mammals.